Sub-Acute Toxicity Study of a Type-I Pyrethroid Permethrin on Testis of Mus Musculus: Pharmaceutical Science-Pharmacology for Drug Discovery - Zeba Siddiqui; Ketaki Desai (International Journal of Life Science and Pharma Research, 2022)
Pesticide usage has witnessed a rise in the current years to overcome the glitches of food scarcity because of incessant increase in population. Regardless of its extensive use in agriculture and related fields, these should be properly and thoroughly investigated because of unexplored danger which they bring along. The present investigation deals about the effects of one such pesticide, Permethrin, belonging to the class of synthetic pyrethroids, having broad range application in the field of agriculture, as an insect repellent, in lice shampoos, in the treatment of scabies and numerous other commercial uses. Although few reports have documented its adverse effect on the vital organs in different experimental models, there still persist lacunae in literature about its effect on the male reproductive tissue. Hence, the present study was aimed to evaluate the effects of Permethrin on the male reproductive gonad of Swiss albino mice. Permethrin (130 mg/kg body weight) was administered orally for a period of 21 days after which the biochemical parameters in testis were assayed. The results showed that Permethrin administration lowered the gravimetric indices (body weight p<0.002, organ weight p<0.001) and decreased the levels of protein (p<0.001) and cholesterol (p<0.001), which is an important precursor in the formation of androgens. Essential enzymes like 3β and 17β hydroxysteroid dehydrogenase which are pivotal in the steroidogenesis pathway were also found to be depleted (p<0.001 and p<0.002 respectively). These findings were further confirmed by the histopathological analysis and indicated that Permethrin had negative effects on the male reproductive system and can be one of the contributing factors leading to infertility.